Deep Learning Implementation For Strengthening Islamic Values And Learning Enthusiasm In Elementary Students - Ima Lutfiasari; Hawwin Fitriyani (International Journal of Science and Environment (IJSE), 2026)
This study was motivated by the importance of learning that is not only orientedtoward academic achievement but is also able to strengthen Islamic values andstudents’ learning enthusiasm. The learning process in elementary schools is stilloften dominated by conventional teacher-centered methods, so student engagement,value internalization, and learning motivation have not been optimal. This conditionrequires the application of a more meaningful, active, and contextual learningapproach. This study aims to analyze the implementation of deep learning instrengthening Islamic values and increasing students’ learning enthusiasm atLukman Al Hakim Islamic Elementary School Kendal. This study employed aqualitative approach with a descriptive field research design. The researchinformants consisted of the principal, vice principal for curriculum affairs, teachers,educational staff, and students. Data were collected through observation,interviews, and documentation. Data analysis used the Miles, Huberman, andSaldaña model through data reduction, data display, and conclusion drawing. Datavalidity was tested through source, technique, and time triangulation. The resultsshowed that the implementation of deep learning was carried out through studentcentered learning, active discussions, group work, learning reflection, andconnecting learning materials with real-life contexts. The internalization of Islamicvalues was conducted through religious habituation, teacher role modeling, strengthening honesty, discipline, responsibility, empathy, and integrating valuesinto learning materials. Changes in students’ learning enthusiasm were indicated byincreased enthusiasm, courage to ask questions, persistence in completing tasks,and higher interest in learning. The conclusion confirms that deep learning is aneffective approach in integrating academic quality, strengthening Islamic values,and enhancing students’ learning enthusiasm in Islamic elementary schools.